Pregnancy Preeclampsia in Patients with a History of Chronic Disease and Complications - Nguyen Huc Dung (Newinera Publisher, 2022)
A condition known as preeclampsia is a pregnancy-related problem that carries with it the risk of death. Those pregnant women who have a history of obstetric complications have a risk that is 1,275 times greater than those pregnant women who do not have such a history. This was shown by the fact that a correlation exists between the two different groups. The presence or absence of pregnancy in a woman may have an impact on whether or not she is at risk of getting diabetes. There has been a shift in the proportion of carbohydrates that are present in the body of the mother ever since it was discovered that she was expecting a child. Diabetes is a condition that may be harmful to a pregnancy regardless of whether it is present before birth or if it is acquired during pregnancy.